2018
DOI: 10.1016/s0140-6736(18)30102-8
|View full text |Cite
|
Sign up to set email alerts
|

Progress in clinical research in surgery and IDEAL

Abstract: The quality of clinical research in surgery has long attracted criticism. High-quality randomised trials have proved difficult to undertake in surgery, and many surgical treatments have therefore been adopted without adequate supporting evidence of efficacy and safety. This evidence deficit can adversely affect research funding and reimbursement decisions, lead to slow adoption of innovations, and permit widespread adoption of procedures that offer no benefit, or cause harm. Improvement in the quality of surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 17 publications
0
59
0
2
Order By: Relevance
“…As stated in the IDEAL framework, a new innovation or technique should be evaluated stepwise, and not be implemented broadly before standardized indications and procedures have been developed. In this way, adverse effects and consistent outcomes can be established during the learning curve, which new centres can set as a benchmark 37 . The surgical community should focus on demonstrating oncological safety rather than surrogate endpoints for new innovative surgical techniques for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As stated in the IDEAL framework, a new innovation or technique should be evaluated stepwise, and not be implemented broadly before standardized indications and procedures have been developed. In this way, adverse effects and consistent outcomes can be established during the learning curve, which new centres can set as a benchmark 37 . The surgical community should focus on demonstrating oncological safety rather than surrogate endpoints for new innovative surgical techniques for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The initial IDEAL publication 21 , however, was largely theoretical with little practical guidance about how PFS should be performed. Recently published updated IDEAL recommendations 22 now provide some clarification regarding the role of PFS in surgery as a result of recognition that the original IDEAL guidance published in 2009 21 had little impact on the design and conduct of surgical PFS 37 . The updated IDEAL framework 22 suggests several feasibility issues to consider in stage 2a/2b studies, including estimating effect size, defining intervention quality and standards, evaluating learning curves, exploring subgroup differences, eliciting key stakeholder values and preferences, and analysis of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results provide insight into the promising role of the funder as a driver to improving the, long criticized, surgical evidence base. The funder, who has influence over whether and how studies are carried out and has been suggested as a driver for improving the quality of research during the period of growth for surgical trials [3], can play a valuable role in ensuring that future trials do not have the same shortfalls as those in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) are recognized as providing the highest level of evidence, second only to systematic reviews of such trials [1]. The need for surgical randomized trials is well recognized [2,3], and this has led to a push for growth in recent years [3,4]. Leading research organizations are supporting this growth through establishing a number of initiatives and research objectives, ultimately aiming to improve the global surgical evidence base [5e10].…”
Section: Introductionmentioning
confidence: 99%